EVALUASI PENERAPAN KESELAMATAN DAN KESEHATAN KERJA (K3) PADA PROYEK GATEWAY PASTEUR APARTEMENT BANDUNG - Firdaus, Alfi (2014)
Keselamatan dan Kesehatan Kerja (K3) is an important thing which has to be considered in a contruction work. The accidents are surely become problems for continuity of the project. The disadvantage is not only the loss of materials but also there will be victims in large numbers. Therefore, K3 needs to be applied in projects, one of the projects is Gateway Pasteur Apartement Bandung. The researcher makes an observation about K3 there, which aims to discovery the application of K3, the management of K3, and RAB of K3 in that project. K3 is a program which ensures employees safety and health in workplace. Through this observation, then the data are obtained, which are interview and legislation of K3. The application of K3 at Gateway Pasteur Apartement Bandung is good because 84,81 at the project obey to the procedures which have been applied by legislation. The employees obey to the rules, which are applied in that project, because the control from the site engineer. Social security for the employees is using JAMSOSTEK, however the employees are